Variabilidade intra-específica em Lithraea molleoides (Vell.) Eng. (Aroeira-Branca) a partir dos processos de germinação e emergência - Berger, Ana Paula de Aguiar (2007)
The great diversity of morphology in diaspores of Anacardiaceae reflects in germination and dormancy processes and generates a differentiated behavior among species. There are some species within this family that show physical dormancy, others show mechanical dormancy, some that do not show dormancy and also species that lack this information in the available literature. Lithraea molleoides is among the species whose dormancy has not yet been elucidated. The objective of this work was therefore to study germination and emergence of seedlings originated from diaspores recently collected from different donor plants occurring in the Rio Araguari Valley, MG, as well as behavior of diaspores after storage in cold chamber. Diaspores were collected from eight donor plants in October and November, 2004 and 2005. Six experiments were carried out, being two with recently-collected diaspores, two with diaspores stored for six months in cold chamber and two with diaspores stored for 12 months in the same condition. The experiments were conducted under controlled laboratory conditions and uncontrolled conditions of a semi-open greenhouse. Data collection was carried out every 24 h, by recording embryo protrusion (botanical criteria) in the laboratory experiments and seedling hypocotyl emergence above the substrate in the greenhouse experiments. In all the experiments, the diaspores derived from donor plant number 2 stood out in some way, showing better physiological quality compared with the others (average time between 4 and 22 days, average speed between 0.042 and 0.217 day-1, uncertainty between 1.62 and 3.53 bits and synchrony between 0.040 and 0.381). The large values of average time and uncertainty, as well as low synchrony, indicate that the processes of germination and seedling emergence of Lithraea molleoides, independently of diaspore age, are dispersed in time, characterizing them as exhibiting relative dormancy and being resistant to dry storage. It is worth emphasizing that the study of the sample population of this species was representative, since the collected donor plants showed similar behavior in all experiments. These characteristics are important for the species conservation.